2011
DOI: 10.1590/s1413-86702011000600004
|View full text |Cite
|
Sign up to set email alerts
|

Risk of coronary artery disease in individuals infected with human immunodeficiency virus

Abstract: There is a high prevalence of risk factors for CAD in the studied population, with dyslipidemia being the most frequent. HDL-cholesterol and triglycerides were the most frequently altered factors and were associated with the use of protease inhibitors. Risk assessed by the FRS was low in most cases. CACS > 0 was found in 32.5%, demonstrating the need to re-evaluate the strategies for assessing cardiovascular risk in the HIV-infected population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Globally, studies have reported varying prevalence of obesity among adult PLHIV, ranging from 6.8% to 34%. [ 6 7 8 9 ] However, a study conducted in South India (Vellore) reported a prevalence similar (23.6%) to the current study. [ 10 ] Prevalence of abdominal obesity found in our study was also similar to the study conducted in Vellore.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Globally, studies have reported varying prevalence of obesity among adult PLHIV, ranging from 6.8% to 34%. [ 6 7 8 9 ] However, a study conducted in South India (Vellore) reported a prevalence similar (23.6%) to the current study. [ 10 ] Prevalence of abdominal obesity found in our study was also similar to the study conducted in Vellore.…”
Section: Discussionsupporting
confidence: 74%
“…Increased prevalence of co-existing cardiovascular risk factors in HIV patients like tobacco or alcohol use might also be an important reason. [ 6 7 8 ] An increased incidence of myocardial infarction has also been observed in persons with HIV. [ 9 ] Hence, ART might need to be tweaked depending on the metabolic profile of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Literature really points to the fact such behavior is due to HIV infection and its treatment -ART use (Koenig, 2017;Lang et al, 2015;Vilela et al, 2011)-, with inflammation and immunological activation widely proven as HIV infection part, contributing to CAD emergence (Boettiger et al, 2020;Freiberg et al, 2013;Vachiat et al, 2017). In fact, a large cohort found a strong association of HIV-positive individuals along increased risk of MI, regardless of traditional risk factors (Katoto et al, 2018;Silverberg et al, 2014).…”
Section: Discussionmentioning
confidence: 99%